Competition effects with mixed stands of wheat and kochia (Kochia scoparia) biotypes resistant and susceptible to acetolactase synthase inhibitor herbicides (Scientia Agricola, 1994)
Greenhouse experiments were conducted to compare the competitive ability of sulfonylurea resistant and susceptible kochia (Kochia scoparia L. Schard) compared to wheat. The results of several replacement series experiments indicate that wheat was the dominant competitor, and an average of one wheat plant reduced resistant kochia yield per plant equal to the effect of 4.8 resistant kochia or 5.4 susceptible kochia plants. Intraspeciflc competition was more important than interspecific competition for wheat, whereas the reverse was true for the resistant and susceptible kochia. The results of the niche differentiation index (NDI) indicate that wheat and either resistant or susceptible kochia are only partly limited by the same resources. The resistant and susceptible kochia, however, are limited by the same resources.